The Potential Regulatory Mechanism of lncRNA 122K13.12 and lncRNA 326C3.7 in Ankylosing Spondylitis - Wang, Jian-xiong; Jing, Feng-yang; Xu, Yue-chen; Zong, He-xiang; Chu, Yi-ran; Wang, Cong; Chen, Ke-ming; Tong, Wan-qiu; Wang, Xi-le; Xu, Sheng-qian (Frontiers in Molecular Biosciences, 2021)
This work aims to analyze and construct a novel competing endogenous RNA (ceRNA) network in ankylosing spondylitis (AS) with bone bridge formation. lncRNAUsing RNA sequencing and bioinformatics, we analyzed expression profiles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and mRNA in whole blood cells from 5 AS patients and 3 healthy individuals. Next, we verified the expression levels of candidate lncRNAs in 97 samples using the ΔΔCt value of real-time quantitative polymerase chain reaction (qRT-PCR). We used multivariate logistic regression analysis to screen lncRNAs and clinical indicators for use in the prediction model. Both SPSS 24.0 and R software were used for data analysis and prediction model construction. The results showed that compared with the normal controls, 205 long non-coding RNAs (lncRNAs), 961 microRNAs (miRNAs), and 200 mRNA (DEmRNA) were differentially expressed in the AS patients. We identified lncRNA 122K13.12 and lncRNA 326C3.7 among 205 lncRNAs differentially expressed between AS patients and healthy humans. Then, we noted that 30 miRNAs and 5 mRNAs formed a ceRNA network together with these 2 lncRNAs. These ceRNA networks might regulate the tumor necrosis factor (TNF) signaling pathway in AS development. In addition, the expression level of lncRNA 122K13.12 and lncRNA 326C3.7 correlated with various structural damage indicators in AS. Specifically, the lncRNA 326C3.7 expression level was an independent risk factor in bone bridge formation [Area under the ROC curve (AUC)=0.739 (0.609–0.870), P=0.003], and the best Youden Index was 0.405 (sensitivity=0.800 and specificity=0.605)]. Moreover, we constructed a lncRNA-based nomogram that could effectively predict bone bridge formation [AUC=0.870 (0.780–0.959), P<0.001, the best Youden Index was 0.637 (sensitivity=0.900 and specificity=0.737)]. In conclusion, we uncovered a unique ceRNA signaling network in AS with bone bridge formation and identified novel biomarkers and prediction models with the potential for clinical application.